2023
DOI: 10.1038/s41598-023-29684-9
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics construction and experimental validation of a cuproptosis-related lncRNA prognostic model in lung adenocarcinoma for immunotherapy response prediction

Abstract: Cuproptosis is a newly form of cell death. Cuproptosis related lncRNA in lung adenocarcinoma (LUAD) has also not been fully elucidated. In the present study, we aimed to construct a prognostic signature based on cuproptosis-related lncRNA in LUAD and investigate its association with immunotherapy response. The RNA-sequencing data, clinical information and simple nucleotide variation of LUAD patients were obtained from TCGA database. The LASSO Cox regression was used to construct a prognostic signature. The CIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…Additionally, several research reported GSEC could promote the malignant process of triple-negative breast cancer and hepatocellular carcinoma via the GSEC/miR-202-5p/AXL axis and the GSEC/miR-101-3p/SNX16/PAPOLG axis [38,39], respectively. Furthermore, lncRNA AL606834.1 has been used for prognostic models of lung adenocarcinoma and pancreatic cancer [40,41], AL365181.2 has been applied in multiple prognostic models of lung adenocarcinoma [42,43], and AC012615.1 has been studied in a prognostic model of glioblastoma [44]. These ndings provided the robust evidence for the construction of our DRLS score based on these 5 lncRNAs.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, several research reported GSEC could promote the malignant process of triple-negative breast cancer and hepatocellular carcinoma via the GSEC/miR-202-5p/AXL axis and the GSEC/miR-101-3p/SNX16/PAPOLG axis [38,39], respectively. Furthermore, lncRNA AL606834.1 has been used for prognostic models of lung adenocarcinoma and pancreatic cancer [40,41], AL365181.2 has been applied in multiple prognostic models of lung adenocarcinoma [42,43], and AC012615.1 has been studied in a prognostic model of glioblastoma [44]. These ndings provided the robust evidence for the construction of our DRLS score based on these 5 lncRNAs.…”
Section: Discussionmentioning
confidence: 82%
“…Additionally, several research reported GSEC could promote the malignant process of triple-negative breast cancer and hepatocellular carcinoma via the GSEC/miR-202-5p/AXL axis and the GSEC/miR-101-3p/SNX16/PAPOLG axis 38 , 39 , respectively. Furthermore, lncRNA AL606834.1 has been used for prognostic models of lung adenocarcinoma and pancreatic cancer 40 , 41 , AL365181.2 has been applied in multiple prognostic models of lung adenocarcinoma 42 , 43 , and AC012615.1 has been studied in a prognostic model of glioblastoma 44 . These findings provided the robust evidence for the construction of our DRLS score based on these 5 lncRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al applied a CRlncRNAs model to evaluate the immune infiltration status in head and neck squamous cell carcinoma [ 39 ]. Li et al demonstrated the potential of CRlncRNAs in predicting immunotherapy response in LUAD [ 40 ]. These findings suggest that CRlncRNAs may serve as promising biomarkers for revealing the complex tumor microenvironment and aiding clinicians in formulating personalized immunotherapy for patients.…”
Section: Discussionmentioning
confidence: 99%